Relationship Between Knowledge And fiber Konsumption With Nutritional Status To The Employess Of Bumi Panua Hospital, Pohuwato Regency: Doi: https://doi.org/10.47918/jhts.v3i1.334 - Rita Amini Warastuti; Sofyan Tambipi; Tulenan, Nola (LP2M Universitas Bina Mandiri Gorontalo, 2021)
Basic Health Research (Riskesdas) 2018 states that the prevalence of obesity or overweight in adults over 18 has continued to increase from year to year since 2007. The formulation of the problem in this study is whether there is a relationship between knowledge and fiber consumption with the nutritional status of the employees of BumiPanua Hospital, Pohuwato Regency. The research aimed to determine whether there was a relationship between knowledge and fiber consumption with the nutritional status of the employees of BumiPanua Hospital, Pohuwato Regency. This research is an observational study conducted with a quantitative approach with a cross-sectional design. This research was conducted for 2 months, from May to June 2020, at BumiPanua Hospital, Pohuwato Regency. The population in this study were 469 employees at BumiPanua Regional General Hospital, Pohuwato Regency, with a total sample of 47 employees. The data analysis technique used is the chi-square test. The results of statistical tests show that there is no relationship between knowledge of fiber and the nutritional status of employees at BumiPanua Hospital of Pohuwato Regency, and there is a relationship between fiber consumption and the nutritional status of employees at BumiPanua Hospital, Pohuwato Regency. The recommendation of the results of this study is the need to consume foods containing fiber in daily consumption with the main sources of plants, vegetables, cereals, fruits, nuts.